2017
DOI: 10.1007/s12519-017-0065-y
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year step-down withdrawal from inhaled corticosteroids in asthmatic children receiving immunotherapy

Abstract: In the present study, we developed a 2-year step-down and withdrawal strategy from ICSs strategy for allergic asthma children receiving SCIT; the strategy was efficacious and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated significant dose- 21,22 and duration-dependent 23 and reversible [24][25][26][27] increases in MCT PC 20 with inhaled corticosteroid treatment (vs placebo). Our findings additionally suggest that LTRAs can cause false negative MCT results.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated significant dose- 21,22 and duration-dependent 23 and reversible [24][25][26][27] increases in MCT PC 20 with inhaled corticosteroid treatment (vs placebo). Our findings additionally suggest that LTRAs can cause false negative MCT results.…”
Section: Discussionmentioning
confidence: 94%
“…One potential benefit of AIT is that children with asthma who complete AIT can successfully step down to lower steps of treatment regimens, ultimately requiring fewer inhaled medications or lower doses of inhaled medications. 21 , 22 Prospective clinical trials are needed to determine whether children with severe asthma can safely use biological medications to initiate immunotherapy, and subsequently discontinue the biological medications as the disease modifying effects of immunotherapy are seen.…”
Section: To the Editormentioning
confidence: 99%